Label-free proteomic analysis of Duchenne and Becker muscular dystrophy showed decreased sarcomere proteins and increased ubiquitination-related proteins - Juliana Cristina Tobar da Silva; Mariângela Rangel Alves Nogueira; Yara Martins da Silva; Fábio César Sousa Nogueira; Nathalie Henriques Silva Canedo; Katia Carneiro; Denise de Abreu Pereira (Scientific Reports)
Abstract Muscular dystrophies (MD) are a group of hereditary diseases marked by progressive muscle loss, leading to weakness and degeneration of skeletal muscles. These conditions often result from structural defects in the Dystrophin–Glycoprotein Complex (DGC), as seen in Duchenne Muscular Dystrophy (DMD) and Becker Muscular Dystrophy (BMD). Since MDs currently have no cure, research has focused on identifying potential therapeutic targets to improve patients’ quality of life. In this study, skeletal muscle tissue samples from DMD and BMD patients, as well as non-dystrophic controls, were analyzed using label-free mass spectrometry (MS/MS) to characterize the proteomic profile of these conditions and identify biomarkers for differential diagnosis. In-silico analysis revealed that dystrophic muscle tissues are linked to biological processes related to cellular energy metabolism, including oxidation of organic compounds, energy production, and cellular respiration. Enrichment of functions associated with cell structure and RNA binding was also observed, including cytoskeletal protein binding and RNA binding. The human phenotypes most related to the proteomic signature were abnormal circulating metabolites, muscle physiology, and weakness. Quantitative analysis identified significant changes in proteins associated with sarcomere organization and protein ubiquitination, such as myomesin, myozenin, and E3 ubiquitin-protein ligase rififylin, suggesting these as potential therapeutic targets.